OP0316 The Association Between Childhood Obesity Measures and Adulthood Knee Pain, Stiffness and Physical Dysfunction: A 25-Year Cohort Study. (23rd January 2014) - Eathakkattu Antony, B. S.; Jones, G.; Venn, A.; Cicuttini, F.; March, L.; Blizzard, L.; Dwyer, T.; Cross, M.; Ding, C.
Abstract : Background: Obesity has been associated with knee pain in both children and adults.[1, 2 ] However, no study has investigated the long-term association between childhood weight and knee symptoms assessed using WOMAC scale in adults. Objectives: The aim of this study was to describe the associations between weight, body mass index (BMI) and overweight in childhood and knee pain, stiffness and physical dysfunction in adults 25 years later. Methods: Subjects broadly representative of the Australian population (n=449, aged 31-41 years, female 47.9%) were selected from the Childhood Determinants of Adult Health study (a long-term follow-up study of Australian Schools Health and Fitness Survey of 1985). Height, weight, and knee injury were recorded, and knee pain was assessed using WOMAC scale. Childhood height and weight were measured according to standard protocols 25 years prior, and BMI and overweight were calculated. Results: Childhood weight, BMI and overweight were significantly associated with the presence of adulthood knee pain when walking on flat surface after adjustment for childhood age, duration of follow-up, sex, height (if weight was the predictor), childhood and adulthood injury. These associations persisted after further adjustment for adulthood corresponding measures (BMI: OR: 1.17, 95% CI: 1.01, 1.36; overweight: OR: 3.35, 95% CI: 1.34, 8.40; weight: OR: 1.07, 95% CI: 1.00, 1.13). Subjects who were overweight in both childhood and adult life had a significant increase in the adulthood walking knee pain (27.3% of subjects, OR: 3.17, 95% CI: 1.06, 9.52) compared with those who had normal weight in both childhood and adult life (walking knee pain: 8.6% in these subjects). These associations were most notable in males. There were no significant associations between childhood obesity measures and total WOMAC knee pain, stiffness and dysfunction scores. However, gender-specific analysis revealed an effect of overweight in childhood on adulthood total WOMAC pain (OR: 2.78, 95%CI: 1.00, 7.72) in males, but this became of borderline significance after adjustment for adulthood overweight. In males, childhood weight and BMI were associated with greater total WOMAC stiffness (BMI: OR: 1.25, 95% CI: 1.07, 1.45; weight: OR: 1.08, 95% CI: 1.02, 1.15) and physical dysfunction (BMI: OR: 1.22, 95% CI: 1.06, 1.41; weight: OR: 1.07, 95% CI: 1.01, 1.13) independent of adulthood weight and BMI. Conclusions: Childhood obesity measures were significantly associated with adulthood mechanical knee joint pain, knee stiffness and physical dysfunction mainly in men, independent of the adult obesity measures. These indicate the importance of reducing childhood obesity in preventing adulthood knee symptoms. References: Jinks C, Jordan KP, Blagojevic M, Croft P. Predictors of onset and progression of knee pain in adults living in the community. A prospective study. Rheumatology (Oxford). 2008 Mar; 47(3):368-374. Deere KC, Clinch J, Holliday K, McBeth J, Crawley EM, Sayers A, et al. Obesity is a risk factor for musculoskeletal pain in adolescents: findings from a population-based cohort. Pain. 2012 Sep; 153(9):1932-1938. Acknowledgements: The National Health and Medical Research Council (NHMRC) of Australia funded this study. Special thanks go to the subjects who made this study possible. The roles of Liz O'Loughlin and Judy Hankin in collecting the data, Marita Dalton in managing the database and Petr Otahal in statistical analyses are gratefully acknowledged. C. Ding is a recipient of ARC Future Fellowship, G. Jones is a recipient of a NHMRC Practitioner Fellowship, L. Blizzard is a recipient of a NHMRC Career Development Fellowshipand and A. Venn is a recipient of a NHMRC Research Fellowship. None of the authors have any conflict of interest to declare. Disclosure of Interest: None Declared